Changes in the abundance and distribution of a montane specialist bird, the Dotterel Charadrius morinellus, in the UK over 25 years - Hayhow, Daniel B; Ewing, Steven R; Baxter, Alistair; Douse, Andy; Stanbury, Andrew; Whitfield, D. Philip; Eaton, Mark A (Bird study, 2015)
Capsule The number of Dotterel breeding in the UK declined by 57% between 1987/88 and 2011, from 980 to 423 breeding males; there has been a contraction of the species’ geographical range as well as declining numbers on core sites. Aims To estimate the number of Dotterel breeding in the UK in 2011, the changes since surveys in 1987–88 and 1999, and to document broad patterns of change in distribution. Methods Two survey visits were carried out at montane sites (protected areas designated for Dotterel; and a stratified random sample of other sites >600 m altitude) across the Dotterel's breeding range using a standardized protocol as used in previous surveys. The first visit was to assess numbers in the pre-breeding period, and the second visit, comparable to those made in previous national surveys, provided data to calculate population estimates through extrapolation to unsurveyed sites and 95% confidence intervals by bootstrapping. Results In 2011, the number of Dotterel in the UK was estimated to be 423 breeding males (95% CI 279–644), a decline of 57% since 1987/88 and 43% since 1999. As in previous surveys, the majority of the population (61%) was found in the East Highlands, but large declines were recorded in this region. Dotterels were largely absent from previously occupied sites in North and West Highlands. Conclusions Numbers of Dotterel breeding in the UK declined by more than half between 1987 and 2011. Long-term monitoring data are rare for montane environments in the UK, but these findings may signify the occurrence of important ecological changes, with possible drivers including land-use/habitat change, nitrogen deposition and climate change.